Variations of Surface Properties of Corona Treated Wool - Talebian, Aazam; Nourbakhsh, Shirin; Ghaffar Ebadi, Abdol; Valipour, Peiman (Asian Journal of Chemistry, 2010)
Plasma and corona treatments as environmentally friendly processes modify the superficial properties of textile fibers without any damage to the bulk properties of the material. In this study, wool fabric was exposed to corona treatment in different powers and passages. The effect of corona treatment was investigated on the wettability, dye ability, mechanical and surface properties of wool fabric. Corona treatment leads to reduce acid dye exhaustion of wool fabric and increase the tensile strength and Young modulus. SEM micrographs show the etching effect of corona treatment and removing the edge of wool scales. FT-IR spectra indicate to surface functional groups variation of treated wool fabric.